Analisis Efektivitas Mesin Fluidized Bed Dryer dengan Metode Overall Equipment Effectiveness dan Fault Tree Analysis di PT XZY - Talitha Palupi Bratandari; Endang Pudji Widjajati (Pusat Riset dan Inovasi Nasional, 2023)
PT XZY is a company that processes industrial salt in the Gresik area, East Java. During the production process, there are still some obstacles found in the machine, especially in the fluidized bed dryer machine. With several obstacles such as problematic fans, unstable fan rotation, temperature sensors not working, and others that can hamper the production process so that the machine experiences downtime which results in reduced machine effectiveness. The purpose of this study is to determine the value of machine effectiveness using the OEE method then find the most dominant type of losses for decreasing machine effectiveness and to analyze the root cause of failure in fluidized bed dryer machine components. The calculation results show that the OEE value of PT XZY is 58.25%, which is relatively normal but can still be improvised a lot. The most dominant type of losses for decreasing machine effectiveness is idling and minor stoppage losses with an average of 43.47%. Then for the root of the problem there is damage to the fluidized bed dryer engine components due to lack of discipline in maintenance, engine components are eroded to breaks, lubricants run out, excessive raw materials, incorrect operation, scuffed / chipped cables, and electricity failure.